Actual y futura disponibilidad del agua en un contexto de inseguridad hídrica en la subcuenca de Parón, cuenca del río Santa, Perú - Izaguirre Liviac, Marcos Fabio (2024)
Water security in Andean watersheds depends on adaptive water management in the face of glaciohydrological and socioeconomic impacts. The Parón sub-basin in the Santa River basin (Ancash, Peru) is a suitable case in this respect. Water is regulated by a floodgate in the Parón lake, which has become a focal point of social conflict. This study analyzes the water balance of this sub-basin using a semi-distributed hydrological model for the present (2006-2016) and future (2030-2050), considering different scenarios of precipitation variation, glacial melting, and increased water demand. Without regulation of the lake, the sub-basin would enter into a strong water deficit in the dry months (June-August). Until 2030 (2050), assuming a maximum regulation of 2.6 m³/s, a 15% (35%) increase in precipitation, and a 10% (26%) decrease in the glacier contribution to the annual flow, water availability would be reduced by 37% (35%). In a pessimistic scenario with a 15% (35%) decrease in precipitation, water availability would still be reduced by 47% (56%) annually. These results highlight the need to keep a socially acceptable minimum water flow (>2 m³/s) to avoid critical levels of water scarcity in the dry months and to address the needs of local water users.